Strategi Dinas Kehutanan Provinsi Sulawesi Selatan Dalam Mengatasi Alih Fungsi Lahan Hutan Di Wilayah Kabupaten Gowa - Arhamullah, Arhamullah; Abdi, Abdi; Fatmawati, Fatmawati (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2021)
ABSTRACTThis study purposed to find out the strategy of the forestry service of shout Sulawesi Province in overcoming the conversation of forest land function in Gowa Regency and to find out what factors influence the conversion of land functions in Gowa Regency. This study used a qualitative research with a descriptive type. The number of informants in this study amounted to 6 people who were deternined positively. The results showed that the strategy of the south Sulawesi Provincial Forestry service in overcoming the conversion of forest land function in the Gowa Regency area was to set annual goals, a forest management plan was a plan that included all aspects of forest management in the long and short term. The factors that influenced the conversion of forest land in Gowa Regency were economic factors, educational factors, and domographic factors.Keywords: strategic management, strategy, forest management.